Peran Guru Bimbingan Konseling Dalam Mengatasi Ketidak Disiplinan Siswa MTs Mamba’ul Khoiriyatil Islamiyah Bangsalsari - Dina Fardaniah; Erlinda Eka Maeliyanti; Ulya Nur Maulidia; Ani Qotuz Zuhro’ Fitriana (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
This study aims to find out how the role of guidance and counseling teachers is in overcoming student indiscipline at MTs Mamba'ul Khoiriyatil Islamiyyah Bangsalsari. This study uses a qualitative approach that is descriptive, data collection techniques using interviews, observation, and case studies. The role of the BK teacher in overcoming indiscipline does not immediately make decisions and immediately give punishment, the BK teacher solves it by first identifying the problem with a persuasive approach, then grouping the problem according to the level of the violation committed, then if the violation is intolerable or it includes serious violations of the counseling teacher also involving the homeroom teacher or school structure such as student assistants.Abstract ditulis dalam bahasa Inggris dan bahasa Indonesia (kecuali artikel yang ditulis dalam bahasa Inggris) yang berisikan isu-isu pokok, tujuan penelitian, metode/pendekatan dan hasil penelitian. Abstrak ditulis dalam dua bahasa yaitu Bahasa Inggris dan Bahasa Indonesia, maksimal 200 kata dalam bahasa Inggrisdan150 kata dalam bahasa Indonesia. Abstrak ditulis dengan Times New Roman9, spasi 1, bercetak lurus dan dengan format satu kolom. (Times New Roman 9, spasi tunggal, dan cetak miring), maksimal 1 halaman.